Procedures and compliance of a video modeling applied behavior analysis intervention for Brazilian parents of children with autism spectrum disorders. (July 2017) - Bagaiolo, Leila F; Mari, Jair de J; Bordini, Daniela; Ribeiro, Tatiane C; Martone, Maria Carolina C; Caetano, Sheila C; Brunoni, Decio; Brentani, Helena; Paula, Cristiane S
Video modeling using applied behavior analysis techniques is one of the most promising and cost-effective ways to improve social skills for parents with autism spectrum disorder children. The main objectives were: (1) To elaborate/describe videos to improve eye contact and joint attention, and to decrease disruptive behaviors of autism spectrum disorder children, (2) to describe a low-cost parental training intervention, and (3) to assess participant's compliance. This is a descriptive study of a clinical trial for autism spectrum disorder children. The parental training intervention was delivered over 22 weeks based on video modeling. Parents with at least 8 years of schooling with an autism spectrum disorder child between 3 and 6 years old with an IQ lower than 70 were invited to participate. A total of 67 parents fulfilled the study criteria and were randomized into two groups: 34 as the intervention and 33 as controls. In all, 14 videos were recorded covering management of disruptive behaviors, prompting hierarchy, preference assessment, and acquisition of better eye contact and joint attention. Compliance varied as follows: good 32.4%, reasonable 38.2%, low 5.9%, and 23.5% with no compliance. Video modeling parental training seems a promising, feasible, and low-cost way to deliver care for children with autism spectrum disorder, particularly for populations with scarce treatment resources.